Effect of lanthanum on the catalytic properties of PtSn/γ-Al2O3 bimetallic catalysts prepared by successive impregnation and controlled surface reaction. - Del Angel Montes, Gloria Alicia; Bonilla Barenca, Alfredo; Peña Méndez, Yolanda; Navarrete Barbosa, Juan Ignacio; García Fierro, José Luis; Acosta, D. R. (Universidad Autónoma Metropolitana-Iztapalapa, 2003)
Bimetallic PtSn/γ -Al2O3–La2O3 catalysts were prepared by two comparative methods, successive impregnation (SI) and controlled surface reaction (CSR). FTIR-pyridine adsorption revealed a decrease in support acidity as a function of lanthanum content. Oxidized Pt2+ was identified by CO-FTIR chemisorption and by XPS spectra on catalysts prepared by SI. When the CSR preparation method was used, reduced Pt0 was observed and oxidized Pt2+ was not detected. As the lanthanum content increased a diminution in cyclohexane dehydrogenation and n-heptane conversion was observed. Low hydrogenolysis and high selectivity to C7-olefins were obtained in both preparations. It is proposed that lanthanum in SI catalysts stabilizes the platinum in an oxidation state, Pt2+, and diminishes the support acidity. In CSR preparations the lanthanum effect is limited to inhibit the support acidity and hence to the bifunctional reactions occurring during the n-heptane conversion.